2022
DOI: 10.3390/ani12141835
|View full text |Cite
|
Sign up to set email alerts
|

Rumination and Activity Patterns in Angus and Angus-Cross Beef Calves: Influences of Sex, Breed, and Backgrounding Diet

Abstract: The objectives of this study were to evaluate the influences of sex, breed, and backgrounding diet on rumination and activity patterns in Angus and Angus-cross beef calves; and the daily variations in rumination and activity in Angus and Angus-cross beef calves under different backgrounding systems. A total of 62 freshly weaned calves were vaccinated and randomly stratified by sex (heifers and steers), breed (Angus and Angus × Simmental cross), and assigned randomly to 3 backgrounding treatments for 55 days. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 64 publications
1
5
0
Order By: Relevance
“…Similarly, between week 8 and week 20: the third peaks occurred right after the starting of the afternoon milk timeslot (15h30), and the relative stable height of the third peaks indicated the normal activity level caused by the feeding; the difference of heights between the first and the third peaks narrowed down gradually as calves grew older, till the third peaks reached to similar heights as the first peaks at week 19 and week 20, suggesting that the calves were more eager to access to AMFs in the morning as they grew older. Our results were in line with recent studies reporting, that the activity patterns were related to the feeding time in calves (Omontese et al, 2022;Giannetto et al, 2023).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Similarly, between week 8 and week 20: the third peaks occurred right after the starting of the afternoon milk timeslot (15h30), and the relative stable height of the third peaks indicated the normal activity level caused by the feeding; the difference of heights between the first and the third peaks narrowed down gradually as calves grew older, till the third peaks reached to similar heights as the first peaks at week 19 and week 20, suggesting that the calves were more eager to access to AMFs in the morning as they grew older. Our results were in line with recent studies reporting, that the activity patterns were related to the feeding time in calves (Omontese et al, 2022;Giannetto et al, 2023).…”
Section: Discussionsupporting
confidence: 94%
“…This is a new approach as previous studies typically describe activity either in minutes per day (e.g. Omontese et al, 2022), or display average calf activity (standing or lying) across the day on a graph, without extracting key features (Webb et al, 2012(Webb et al, , 2014(Webb et al, , 2015 based on direct manual observations). The added value of the smooth curves is that they represent the expected increase in variables for specific moments of the day when all other parameters in the model are fixed (partial effects are adjusted or scaled variables adjusted for all other variables, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the observed RT values of the 4 h/d period from 57 to 63 days of age and 7 h/d from 63 to 72 days of age are in line with the RT values observed by Lopreiato et al [ 51 ] using Hr-Tag loggers in calves at the same age. In the study of Omontese et al [ 24 ], an average RT of 9 h/d was reported in older calves. At the age of 10 weeks, rumination was well developed, similar to adult cows [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…In short, rumination data were recorded in minutes per 1 h interval as an arbitrary number determined using a three-dimensional accelerometer that recorded the speed and angle of the ear movements. Data were transmitted from the ear tag every 20 min where the system software reported the rumination time using a series of internal algorithms, which are proprietary to Allflex [ 23 , 24 ]. Rumination time data (min/h) were processed to calculate rumination time over the entire trial and the average of rumination time in each of the following periods: 8 to 21 d, 22 to 42 d, 43 to 56 d, 57 to 63, and 64 to 72 days of age.…”
Section: Methodsmentioning
confidence: 99%
“…(2018) using Hr-Tag loggers in calves at the same age during a weaning study. In the test by(Omontese et al 2022), the ear sensors recorded in older calves, speci cally around 3 months of age, an average RT equal to 9 h/d.…”
mentioning
confidence: 99%